The Attitude of CNN Indonesia Online Media in Reporting Corruption Cases in Indonesia - Namira Az-Zahra; Erikson Saragih; Fathul Jannah Harahap (Faculty of Humanities, Universitas Jenderal Soedirman, 2025)
This study aims to reveal the types of language attitude employed by the online media outlet CNN Indonesia in reporting corruption cases in Indonesia and to analyze how ideological messages are represented through the use of such attitudes. The research adopts a qualitative approach with a descriptive method. The analysis is conducted using the Appraisal theory, particularly the subsystem of attitude, which encompasses affect, judgement, and appreciation. The data consist of clauses containing evaluative attitudes drawn from 15 CNN Indonesia news texts on corruption cases published between January 1 and December 31, 2024. The data were collected through documentation, observation, and note-taking techniques, and analyzed using an interactive model. The findings indicate that the use of attitude is dominated by the judgment category (65%), particularly within the subcategory of propriety, which evaluates perpetrators of corruption as unethical, immoral, and irresponsible. Additionally, positive judgment is used to legitimize law enforcement agencies as professional and credible actors. The appreciation category (29%) is used to assess the social, economic, and ecological impacts of corruption. In comparison, affect (6.27%) is rarely applied and more frequently appears implicitly to reinforce the negative image of the perpetrators. These findings suggest that language attitude functions not only as a linguistic evaluative tool but also as an ideological strategy through which the media frames perpetrators as